Development of 2013 Curriculum Learning Model based on Trigger Powerpoint Media to Improves Students’ Creative Thinking Skill - Andri Rahadyan; Ek Ajeng Rahmi Pinahayu; Indra Kurniawan; Rahman Abdilah; Nurfidah Dwitiyanti (EduMa: Mathematics education learning and teaching, 2019)
This research is to develop 2013 curriculum learning model using trigger Microsoft power point. This is an innovative learning model in order to enhance students’ creative thinking skill in mathematics problem solving. The research method is RND with qualitative research using data collecting techniques such as cheque list, observation, questioner, and problem-solving task. The sample of this research is primary students. The processes of developing this model are (a) initial investigation phase is to study literatures and collect the information, (b) design phase is to design the syntax of this model and create the lesson plans, worksheets, and learning materials, (c) realization phase is to do the syntax of this model and the learning materials, and (d) trial, evaluation, and revision phase is the syntax and the learning materials are validated by some validators, do some revisions, then these are evaluated or tried out in a class. This research results a valid, effective, and practical learning model that is able to enhance students’ creative thinking skill in mathematics problem solving. Thus, the 2013 curriculum using trigger Microsoft power point is a learning model that can be applied in primary school related to 2013 curriculum